Assessing governmental roles in the success of infrastructure projetcs implemented through public-private partnership in Vietnam - Thai, Nguyen Hong; Phu, Tran Quang; Thao, Huynh Thi Yen (Frontiers in Built Environment, 2025)
The demand for diversification of funding sources and promotion of private sector participation in infrastructure development is a necessity in Vietnam. Through the public-private partnership (PPP) model, approximately $30 billion has been mobilized for traffic infrastructure development. However, there are still many shortcomings, and growth has shown signs of stagnation. Many factors contribute to this situation, but one of the fundamental reasons is that the management policies and implementation of PPP projects in Vietnam have significant drawbacks. Based on the research results from both domestic and international sources, as well as practical experience, 20 factors relating to the role of the government in attracting infrastructure development investment projects in Vietnam were identified. Then, these factors can be categorized into five groups through factor analysis, as follows: (1) Establishing a suitable legal/regulatory framework, (2) Creating a favorable investment economic environment, (3) Establishing a coordinating and supporting agency, (4) Selecting appropriate franchise partners, (5) Actively participating in various stages of the project life cycle. Accurately assessing the current situation to develop solutions to resolve practical obstacles will be an important basis for mobilizing investment capital for traffic infrastructure development in Vietnam today.